Gone with the wool eaudiobook - Hechtman, Betty (Yarn Retreat Mystery, 2017)
Every October, thousands of monarch butterflies flock to California's Monterey Peninsula to spend the winter there. To welcome their colorful guests, Cadbury by the Sea holds a weeklong festival complete with a butterfly queen and her court. Eager to show some town spirit, Casey Feldstein finds herself fluttering back and forth between setting up a yarn retreat, baking and helping out at the festival. But when a former butterfly queen is found dead with a knife in her back after a Bless the Butterflies service, Casey must set her loom aside to hook a killer with a score to settle.